Comparative law - Kischel, Uwe (Oxford : Oxford University Press, 2019)
This treatise offers in-depth coverage of comparative law, carefully structured and clearly explained by a leading expert. It is an invaluable resource for students seeking a critical introduction to the field, as well as scholars and practitioners, for whom it offers new insights, structures, and approaches.
This edition previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 14, 2019).
Keywords: Comparative law